Sistem Informasi Geografis Pemetaan Lahan Garapan Serikat Petani Pasundan Kabupaten Garut - Fitri Nuraeni; Asep Deddy Supriatna; Amarullah Bachtiar (Jurnal Algoritma, 2022)
In the current implementation of Agrarian Reform, farmer unions must be able to collect and consolidate data on objects and subjects of Agrarian Reform that will be proposed through an acceleration of Agrarian Reform Priority Locations (LPRA). However, the farmer unions that are members of the Pasundan Farmers Union (SPP), in managing object and subject data, still use paper records, so that data is prone to lose, the lack of access to information about arable land, and the difficulty in conducting location surveys. Therefore, a geographic information system is needed by the Pasundan Farmers' Union in Garut Regency as a source of information on arable land and material for proposed administrative completeness for Agrarian Reform Priority Locations (LPRA), the development of this system uses the Rational Unified Process (RUP) methodology with the stages of inception, elaboration, construction, and transition and using the Unified Modeling Language (UML) modeling. With this geographic information system for mapping arable land, the management of object and subject data within the Pasundan farmers' union in Garut Regency is better and can become fast precise and accurate information.